Answer:
Step-by-step explanation:
-0.25
-1/3
1/4
0.3
Answer:
second difference
Step-by-step explanation:
The differences of the y-values will differ by a common amount.
<u>Example</u>:
y = x^2 for x = 2, 4, 6, 8
y-values are 4, 16, 36, 64
differences of these are 12, 20, 28
differences of these differences are 8 and 8, a common value.
This problem can be represented in a formula with fractions. To make it more simple, we are converting 5m30s to just pure seconds, which = 154 copies in 330 seconds.
You set up the formula like this: 154/330 = x/60. (it is x/60 because you want to know the x amount of copies per 60 seconds)
Cross multiply, you get 330x = 9240. Divide both sides by 330, you get:
x = 28 copies.
The final answer is 28 copies per minute
Answer:
r = 8
Step-by-step explanation:
V = π r^2 h so 383 = r^2 (6)
383 / 6 = r^2
64 = r^2 so
r = 8
Answer:
If m is nonnegative (ie not allowed to be negative), then the answer is m^3
If m is allowed to be negative, then the answer is either |m^3| or |m|^3
==============================
Explanation:
There are two ways to get this answer. The quickest is to simply divide the exponent 6 by 2 to get 6/2 = 3. This value of 3 is the final exponent over the base m. Why do we divide by 2? Because the square root is the same as having an exponent of 1/2 = 0.5, so
sqrt(m^6) = (m^6)^(1/2) = m^(6*1/2) = m^(6/2) = m^3
This assumes that m is nonnegative.
---------------------------
A slightly longer method is to break up the square root into factors of m^2 each and then apply the rule that sqrt(x^2) = x, where x is nonnegative
sqrt(m^6) = sqrt(m^2*m^2*m^2)
sqrt(m^6) = sqrt(m^2)*sqrt(m^2)*sqrt(m^2)
sqrt(m^6) = m*m*m
sqrt(m^6) = m^3
where m is nonnegative
------------------------------
If we allow m to be negative, then the final result would be either |m^3| or |m|^3.
The reason for the absolute value is to ensure that the expression m^3 is nonnegative. Keep in mind that m^6 is always nonnegative, so sqrt(m^6) is also always nonnegative. In order for sqrt(m^6) = m^3 to be true, the right side must be nonnegative.
Example: Let's say m = -2
m^6 = (-2)^6 = 64
sqrt(m^6) = sqrt(64) = 8
m^3 = (-2)^3 = -8
Without the absolute value, sqrt(m^6) = m^3 is false when m = -2